Antiprothrombin antibodies induce platelet activation: A possible explanation for anti‐FXa therapy failure in patients with antiphospholipid syndrome?. (5th May 2021) - Chayoua, Walid; Nicolson, Phillip L. R.; Meijers, Joost C. M.; Kardeby, Caroline; Garcia‐Quintanilla, Lourdes; Devreese, Katrien M. J.; de Laat, Bas; Watson, Stephen P.; de Groot, Philip G.
Abstract: Background: Arterial and venous thrombosis are both common in antiphospholipid syndrome (APS). Recent studies have shown that anti‐factor Xa (FXa) therapy in APS patients leads to a greater number of patients with arterial thrombosis than with warfarin. We hypothesize that this may be due to the lowering of prothrombin levels by warfarin. Objectives: To investigate whether antiprothrombin antibodies induce platelet aggregation and to identify the platelet receptors involved. A second aim was to investigate the effect of reduced prothrombin levels on antiprothrombin antibody‐induced platelet aggregation. Methods: Enzyme‐linked immunosorbent assays were performed to measure binding of antiprothrombin antibodies to prothrombin fragment 1+2 and prothrombin. Platelet aggregation assays in washed platelets were performed. FcγRIIA was immunoprecipitated and tyrosine‐phosphorylated FcγRIIA was measured by western blot. Results: The antiprothrombin antibodies 28F4 and 3B1 had lupus anticoagulant (LAC) activity and caused platelet aggregation in the presence of Ca 2+ and prothrombin. Antiprothrombin antibodies without LAC activity did not activate platelets. Inhibition of Syk and Src kinases and FcγRIIA blocked platelet aggregation. Fab and F(ab')2 fragments of 28F4 were unable to induce platelet aggregation. Immunoprecipitations showed that whole 28F4 immunoglobulin G induced tyrosine phosphorylation of FcγRIIA. Platelet aggregation was significantly reduced when prothrombin levels were reduced from 1 µM to 0.2 µM. Conclusions: Antiprothrombin antibodies with LAC activity are able to activate platelets via FcγRIIA. Decreased prothrombin levels resulted in less antiprothrombin antibody‐mediated platelet aggregation. This may explain the lower incidence of arterial thrombosis in patients treated with warfarin than with anti‐FXa therapy.